2021 PACES expert consensus statement on the indications and management of cardiovascular implantable electronic devices in pediatric patients: Developed in collaboration with and endorsed by the Heart Rhythm Society (HRS), the American College of Cardiology (ACC), the American Heart Association (AHA), and the Association for European Paediatric and Congenital Cardiology (AEPC). Endorsed by the Asia Pacific Heart Rhythm Society (APHRS), the Indian Heart Rhythm Society (IHRS), and the Latin American Heart Rhythm Society (LAHRS) - Shah, Maully J; Silka, Michael J; Avari Silva, Jennifer N; Seshadri Balaji; Beach, Cheyenne M; Benjamin, Monica N; Berul, Charles I; Cannon, Bryan; Cecchin, Frank; Cohen, Mitchell I; Dalal, Aarti S; Dechert, Brynn E; et al. (Cardiology in the young, 2021)
In view of the increasing complexity of both cardiovascular implantable electronic devices (CIEDs) and patients in the current era, practice guidelines, by necessity, have become increasingly specific. This document is an expert consensus statement that has been developed to update and further delineate indications and management of CIEDs in pediatric patients, defined as ≤21 years of age, and is intended to focus primarily on the indications for CIEDs in the setting of specific disease categories. The document also highlights variations between previously published adult and pediatric CIED recommendations and provides rationale for underlying important differences. The document addresses some of the deterrents to CIED access in low- and middle-income countries and strategies to circumvent them. The document sections were divided up and drafted by the writing committee members according to their expertise. The recommendations represent the consensus opinion of the entire writing committee, graded by class of recommendation and level of evidence. Several questions addressed in this document either do not lend themselves to clinical trials or are rare disease entities, and in these instances recommendations are based on consensus expert opinion. Furthermore, specific recommendations, even when supported by substantial data, do not replace the need for clinical judgment and patient-specific decision-making. The recommendations were opened for public comment to Pediatric and Congenital Electrophysiology Society (PACES) members and underwent external review by the scientific and clinical document committee of the Heart Rhythm Society (HRS), the science advisory and coordinating committee of the American Heart Association (AHA), the American College of Cardiology (ACC), and the Association for European Paediatric and Congenital Cardiology (AEPC). The document received endorsement by all the collaborators and the Asia Pacific Heart Rhythm Society (APHRS), the Indian Heart Rhythm Society (IHRS), and the Latin American Heart Rhythm Society (LAHRS). This document is expected to provide support for clinicians and patients to allow for appropriate CIED use, appropriate CIED management, and appropriate CIED follow-up in pediatric patients.